Causal association between matrix metalloproteinases and diabetic neuropathy: a two-sample Mendelian randomization study - Bai, Chao; Yang, Wenwen; Qi, Guangwei; Yang, Liuyu; Wu, Qingrui; Peng, Jieguang; Wang, Ning; Liu, Tao (Frontiers in Endocrinology, 2025)
Objective: Diabetic neuropathy (DN), a common and debilitating complication of diabetes, significantly impairs the quality of life of affected individuals. While multiple studies have indicated changes in the expression of specific matrix metalloproteinases (MMPs) in patients with DN, and basic research has reported the impact of MMPs on DN, there is a lack of systematic research and the causal relationship remains unclear. The objective of this research is to investigate the casual relationship between MMPs and DN through two-sample Mendelian randomization (MR). Methods: Data for this investigation were derived from genome-wide association studies (GWAS) of MMPs and DN. For the analysis using two-sample MR, methods such as inverse variance weighted (IVW), weighted median, weighted mode, and MR-Egger were utilized, with IVW serving as the primary measure for determining causative impacts. To evaluate the analysis' heterogeneity and potential pleiotropy, sensitivity examinations including MR-PRESSO analysis, Cochran's Q test, and the leave-one-out test were conducted. Results: IVW analysis revealed that genetically decreased serum MMP-2 level were causally associated with a high risk of DN (OR = 0.88, 95% CI: 0.79-0.99, P = 0.026). Genetically elevated serum MMP-16 level were causally associated with a high risk of DN (OR = 1.15, 95% CI: 1.01-1.32, P = 0.038). Genetic prediction results showed no causal association between other MMPs (MMP14/17/9/12/7/3) and DN. Sensitivity analyses showed no significant heterogeneity or pleiotropy. Conclusion: In summary, this research uncovered a genetic causal relationship between heightened MMP-16 levels and reduced MMP-2 concentrations, and DN risk. These discoveries offer new perspectives on the role of MMPs in DN etiology and establish a foundational premise for further investigations into MMP-targeted therapeutic interventions.